(untitled) (Jurnal Ilmiah Sains dan Teknologi, 2019)
Developments in the internet is one of the most interesting phenomena in technological advances that occur. Arguably the main aspects in its development is the emergence of electronic commerce (e-commerce) in the business environment. Batik offerings is one of home industry engaged in the production, sales and training offerings batik batik special only just. From the results of direct observation, the author encountered problems that occur include the lack of sales information systems specifically Batik Banten to disseminate the sale so as not to include in Banten course, the unavailability of a facility that serves as a medium for the marketing of products to the public that it is difficult to provide complete information and accurate information on a wide range of products such as those offered in Banten Batikbecause it is still conventionalandthe unavailability of manufacturing sales report in Banten Batik in the reporting process and the frequent difficulty is not timely because it is still done manually or not computerized collecting sales note and write down one by one into a book. The author hopes to help Batik Banten to make the sales information system for selling marketing products that are available over the Internet for online or e-commerce, so entrepreneurs can sell and market its products more broadly and to the employees of the reporting process in order to faster and more accurate.This research method using waterfall method.